Asset Prices in Taylor Rules: Specification, Estimation, and Policy Implications for the ECB - Pierre L. Siklos; Thomas Werner; Martin T. Bohl (Deutsche Bundesbank, 2004)
This paper estimates standard and extended Taylor rules for core countries in the euro area, namely France, Germany and Italy, as well as for the ECB. Forward, backward and forecast-based rules are estimated for a variety of samples since the late 1970s. We are particularly interested in the impact of adding asset prices to the standard Taylor rule specification. Since forward-looking Taylor rules are usually estimated via GMM we perform extensive tests for over-identifying restrictions and instrument relevance, a practice generally eschewed in previous work. We find that asset prices can be highly relevant as instruments rather than as separate arguments in policy rules. Backwardlooking Taylor rules, however, cannot be rejected outright. Forecast-based rules perform best using the root mean squared error metric but produce coefficients implying that central banks may be too aggressive at fighting inflation. Encompassing tests are therefore required to select the ?best? policy rule and these suggest that policy rules need to have a mix of forward and forecast-based elements. Furthermore too aggressive reactions to stock prices in particular would have led to an implausible monetary policy. Hence, asset prices appear at best to serve as indicators of the direction of interest rates and not as a variable that the ECB directly reacts to.
Keywords: E5; E4; 330; reaction function; asset prices; Taylor-Regel; Geldpolitik; Börsenkurs; Wirtschaftspotenzial; Schätzung; Deutschland; Frankreich; Italien